Improving Accounting Skills Through Online Learning: The Role of Basic Accounting Websites - Fahrunisa, Liana; Gunahardi; Sumaryati, Sri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
In the era of digital transformation, future accountants are required to have skills with the demands of the industry. The gap between accounting graduates' competencies and industry demands is still a challenge, especially when it comes to financial report preparation skills. This research aims to determine the effectiveness of bacsite (Basic Accounting Website) as a learning medium in improving participants' accounting skills. This research used a pre-test and post-test-based experimental method in the control group and the experimental group, the results showed that participants who used bacsite experienced a 59% higher increase in accounting skills scores than the control group which only increased 54%. Standard deviation analysis showed that the value distribution of the experimental group was more even, signaling a more consistent understanding among participants. Statistical tests also confirmed a significant difference (p < 0.05) between the two groups, reinforcing evidence that bacsite was effective in supporting accounting learning. In addition to improving technical skills, bacsite also encourages self-regulated learning that is in line with the characteristics of today's digital generation. The number of participants who successfully completed the exam correctly increased by 41.7% compared to the previous class. Bacsite is not only a learning tool, but also an innovative solution in bridging the gap between academia and industry.